Strategic role of corporate transparency: the case of Ukrainian agroholdings - Taras Gagalyuk (International Food and Agribusiness Management Review, 2017)
The paper argues that transparency of large corporate farms operating in transition economies is the factor that affects their competitive position as it helps to preserve access to international equity markets and to reduce uncertainty that arises from imperfect local input markets. We demonstrate that the corporate transparency of large farms is an issue of both public interest and private investor interest and decompose the construct of transparency respectively. Because firms tend to exhibit heterogeneous transparency strategies when facing common sets of pressures, we draw upon four case studies of different Ukrainian agroholdings using the suggested decomposition of the transparency construct. We find that large farms may benefit substantially in the long run if they establish effective corporate governance mechanisms and provide more evidence that they contribute positively to corporate social responsibility and rural development.
Keywords: Q14; Q15; O16; O43; G24; G34; 330; corporate transparency; agroholdings; ownership structure; corporate governance; corporate social responsibility